A Note on the Dynamic Properties of the Hines Inflation Model - Thomas, R. L.; Stoney, P. J. M. (Review of Economic Studies, 1970)
R. L. Thomas, P. J. M. Stoney; A Note on the Dynamic Properties of the Hines Inflation Model, The Review of Economic Studies, Volume 37, Issue 2, 1 April 1970,